S171. EFFECT OF DAOA GENETIC VARIATION ON WHITE MATTER ALTERATION IN CORPUS CALLOSUM IN PATIENTS WITH FIRST-EPISODE SCHIZOPHRENIA. (18th May 2020) - Su, Wenjun; Zhu, Tianyuan; Xu, Lihua; Wei, Yanyan; Zeng, Botao; Zhang, Tianhong; Cui, Huiru; Wang, Junjie; Jia, Yuping; Wang, Jinhong; Goff, Donald C; Tang, Yingying; et al.
Abstract: Background: D-amino acid oxidase activator (DAOA) gene, which plays a key role in glutamatergic transmission and mitochondrial function, is frequently linked with the liability for schizophrenia. In this study, we aimed to investigate whether the variation of DAOA rs2391191 could be associated with alterations in white matter integrity in first episode schizophrenia patients, and whether it influences the association between white matter integrity, cognitive function and clinical symptoms of schizophrenia. Methods: Forty-six patients with first-episode schizophrenia and forty-nine sex, age and education-matched healthy controls underwent diffusion tensor imaging (DTI) and were genotyped for SNP DAOA rs2391191. Tract-based spatial statistics (TBSS) was used to delineate the major fiber tracts that showed significant group difference. Patients underwent pathophysiological assessments using Brief Psychiatric Rating Scale (BPRS) and Scale for Assessment of Negative Symptoms (SANS). Cognitive function assessments were performed by Chinese version of the MATRICS Consensus Cognitive Battery (MCCB). Results: Schizophrenia patients presented lower fractional anisotropy (FA) and higher radial diffusivity (RD) mainly spreading over corpus callosum and corona radiata compared with healthy controls (FWE-corrected p<0.05). Compared with patients carrying G allele, patients with AA genotype showed lower FA in body of corpus callosum, and higher RD in genu of corpus callosum, right superior and anterior corona radiata, and left posterior corona radiata. But there were no significant FA or RD differences between two genotype groups in healthy controls. In patients carrying G allele, mean FA values in body of corpus callosum were positively correlated with working memory, mean RD values in genu of corpus callosum were negatively associated with speed of processing, working memory and composite score of MATRICS Consensus Cognitive Battery (MCCB), whilst there were no significant correlations found in AA homozygotes. Discussion: Abnormal white matter integrity in corpus callosum and corona radiata were replicated among our sample of first episode schizophrenia. Genetic variation of DAOA rs2391191 was associated with this abnormality, with AA homozygotes showing less white matter integrity in corpus callosum. Our findings also suggested that rs2391191influenced the association between white matter integrity and cognitive function of schizophrenia patients. Such results might be due to the process of glutamatergic neurotransmission and mitochondrial function DAOA involves in as pinpointed by previous in vitro studies.